THE SENSE OF AGENCY IN THE USE OF GENERATIVE AI SYSTEMS IN EDUCATION FROM A SOCIAL IDENTITY THEORY APPROACH - Daşcı, Esra; Uludağ, Zeynep (Galenos Yayinevi, 2024)
Social identity theory is widely accepted to explain intergroup relations for any group. Decisions are influenced by people's social identity which moderates the agent’s sense of agency -one’s feelings of controlling their own actions; therefore, both should be considered while investigating human-generative AI interactions and possible challenges that arise from them. This review starts with discussing human-AI interactions in terms of Social Identity Theory; then, focuses on the sense of agency that plays out in human-AI interactions moderated by social identity; and finally, discusses consequences that would be raised from these correlations. Accountability is one of the concerns related to human-AI interaction. The diversity of the users and the data is another concern. We conclude the review by suggesting a future direction for empirical research on social aspects of the sense of agency in human-AI interactions and provide possible solutions to ethical and social concerns regarding the use of generative AI systems.
Keywords: Cognition; Biliş; üretken yapay zeka; kontrol duygusu; sosyal kimlik kuramı; eğitim; gruplararası ilişkiler; çeşitlilik; generative AI; sense of agency; social identitiy theory; educat; on; intergroup relations; diversity